2012
DOI: 10.1073/pnas.1112129109
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia promotes ligand-independent EGF receptor signaling via hypoxia-inducible factor–mediated upregulation of caveolin-1

Abstract: Caveolin-1 (CAV1) is an essential structural constituent of caveolae, specialized lipid raft microdomains on the cell membrane involved in endocytosis and signal transduction, which are inexplicably deregulated and are associated with aggressiveness in numerous cancers. Here we identify CAV1 as a direct transcriptional target of oxygenlabile hypoxia-inducible factor 1 and 2 that accentuates the formation of caveolae, leading to increased dimerization of EGF receptor within the confined surface area of caveolae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
104
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(113 citation statements)
references
References 49 publications
6
104
1
1
Order By: Relevance
“…This occurs at the plasma membrane in a ligand-independent manner in hypoxia. 42 Therefore, we measured the protein level of CAV1 of A549 cells over a 72-h time course and found that CAV1 protein level decreased over time in hypoxia by up to 83% (Fig. 9A), which is consistent with the change in tyrosine phosphorylation of EGFR ( Fig.…”
Section: Cav1 (Caveolin 1) Regulates the Activity Of Egfr Tyrosine Kisupporting
confidence: 70%
See 1 more Smart Citation
“…This occurs at the plasma membrane in a ligand-independent manner in hypoxia. 42 Therefore, we measured the protein level of CAV1 of A549 cells over a 72-h time course and found that CAV1 protein level decreased over time in hypoxia by up to 83% (Fig. 9A), which is consistent with the change in tyrosine phosphorylation of EGFR ( Fig.…”
Section: Cav1 (Caveolin 1) Regulates the Activity Of Egfr Tyrosine Kisupporting
confidence: 70%
“…[21][22][23][24][25] Hypoxia can either promote tumor growth by stimulating the expression of cell survival proteins such as EGFR and antiapoptotic BCL2 family members or inhibit tumor growth by upregulating the expression of cell death proteins such as BNIP3, BAX (BCL2-associated X protein) and BID (BH3 interacting domain death agonist). 25,41,42,55 Furthermore, hypoxia can induce autophagy that has been reported to either inhibit or promote cell death creating a dilemma for developing strategies to kill hypoxic cancer cells. [27][28][29][30][31][32][33][34][35][36][37][38] We found that growth factors might be one of the key factors influencing the function of autophagy in hypoxia by regulating the level of autophagic flux.…”
Section: Discussionmentioning
confidence: 99%
“…Apart of this mechanism, Wang et al showed caveolin-1 (CAV1) to promote ligandindependent activation of EGFR in hypoxic ccRCC cells [86]. CAV1 is a major structural component of caveolae, which are specialized lipid raft microdomains on the cell membrane [87].…”
Section: Hif-independent Regulation Of Erbb Igfr and Fgfr Family Memmentioning
confidence: 99%
“…Under hypoxia, the formation of caveolae increases and some fraction of EGFR in the fluid of cell membrane milieu localizes there. The substantially smaller surface area of caveolae relative to the plasma membrane permits ligandindependent activation of EGFR [86]. This mechanism bypasses the requirement for ligand engagement to initiate receptor activation when ligand availability may be limited [86].…”
Section: Hif-independent Regulation Of Erbb Igfr and Fgfr Family Memmentioning
confidence: 99%
See 1 more Smart Citation